IMPLEMENTASI PROGRESSIVE WEB APPS PADA APLIKASI PENDAFTARAN PESERTA DIDIK BARU DI SMK FARMASI MINASA MULIA CIPUTAT - Sopiyan Apandi; Ayyub Muhammad (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Admission of new learners is an activity that is always held regularly every new school year. The admission process used by SMK Farmasi Minasa Mulia currently still uses the method of coming directly to the school to register. Therefore, this study aims to design a web-based New Student Admissions (NSA) application at SMK Farmasi Minasa Mulia, in order to create a more efficient registration system and make it easier for prospective new students to find information. In its creation, this system applies the concept of Progressive Web App (PWA) using the Extreme Programming method and in designing the system using Unified Modelling Language (UML). The result to be achieved from this study is that the school can easily provide good registration services, as well as provide more complete information about the school and make it easier for prospective students to register.